Role of intra-cellular glucocorticoid regulation in vascular lesion development - Iqbal, Javaid (The University of Edinburgh, 2010)
Atherosclerosis and post-angioplasty neointimal proliferation, which are leading causes of cardiovascular morbidity and mortality, develop as a result of chronic or acute vascular injury producing inflammatory and proliferative responses in the vessel wall. Glucocorticoids, the stress hormones produced by the adrenal cortex, have anti-inflammatory and anti-proliferative characteristics and can also influence systemic cardiovascular risk factors. The systemic levels of these hormones are controlled by the hypothalamic pituitary adrenal axis. However, there is also a tissue-specific pre-receptor regulation of these hormones by the two isozymes of 11β-hydroxysteroid dehydrogenase (11β-HSD); type 1 regenerates active glucocorticoids within the cells and type 2 inactivates glucocorticoids. Whilst it has been shown that the inhibition of 11β-HSD1 has favourable effect on cardiovascular risk factors and the inhibition of 11β-HSD2 results in hypertension; the effect of these enzymes on vascular lesion development is not known. The work described in this thesis tested the hypothesis that 11β-HSD1 inhibition reduces vascular lesion development due to improvement in cardiovascular risk factors, whereas 11β-HSD2 inhibition leads to adverse vascular remodelling. Apolipoprotein-E deficient (ApoE-/-) mice fed on western diet were used to study atherosclerosis, whereas neointimal proliferation was investigated using a well-established mouse model of wire-angioplasty. Vascular lesions were assessed using novel imaging and standard histological techniques. 11β-HSD1 inhibition reduced the size of atherosclerotic lesions and improved markers of plaque stability with a reduction in lipid content and increase in collagen content of the plaques. This was associated with a reduction in weight gain and blood pressure but without any effect on lipid profile. 11β-HSD1 inhibition did not produce any significant effect on neointimal proliferation in C57Bl/6J mice. However in ApoE-/- mice, 11β-HSD1 inhibition reduced neointimal proliferation with corresponding increase in size of patent lumen and with an associated reduction in macrophage content of neointimal lesions. 11β-HSD2 deletion produced an outward remodelling in un-injured vessels but there was no effect on neointimal proliferation after wire-angioplasty. Administration of a selective mineralocorticoid antagonist, eplerenone, reduced neointimal lesions significantly but to a similar degree in both C57Bl/6J and 11β-HSD2-/- mice, associated with a significant reduction in macrophage content of lesions but without any effect on blood pressure. Data in this thesis highlight the potential therapeutic application of 11β-HSD1 inhibition in reducing the size and vulnerability of atherosclerotic plaques and also reduction in neointimal proliferation (and hence post-angioplasty restenosis) in high risk patients with „metabolic syndrome‟ phenotype. The results also indicate that 11β-HSD2 has a limited, if any, role to play in the development of neointimal lesions.
Keywords: atherosclerosis; neointimal proliferation; glucocorticoids; 11β-HSD1; eplerenone